Emotional Intelligence and Spiritual Intelligence on Performance Through Employee Job Satisfaction - Agustinus Numberi; Yasir Attamimi; Tantri Widiastuti (Jurnal Manajemen, 2025)
This study examines the effect of employee job satisfaction on performance at the Ministry of Religious Affairs of Jayapura. A quantitative approach utilizing regression analysis was employed, with data collected through structured questionnaires distributed to a representative sample of employees. The results indicate that job satisfaction has a positive and significant effect on employee performance, as evidenced by a positive beta coefficient. In other words, an increase in job satisfaction leads to improved performance, which aligns with established theories and previous studies. These findings underscore the importance of enhancing job satisfaction to boost overall performance. For organizational leaders and HR professionals, this implies the need to develop strategies such as fair compensation, a comfortable work environment, and career development opportunities. By implementing these measures, organizations can foster a more harmonious and productive workplace, ultimately enhancing both employee well-being and performance.